PENGATURAN DAN PENGAWASAN TERHADAP PUPUK AN-ORGANIK DAN PESTISIDA - Nurcahyo, Edy; Rosidi, Ahmad; Haerani, Yeni (Fakultas Hukum Universitas Nahdlatul Wathan Mataram, 2019)
This article aims to describe the regulation and supervision of the procurement, distribution and use of inorganic fertilizers and pesticides in crop cultivation. The number of plants consumed by humans becomes important to maintain the quality of plants in the cultivation of these plants. The research method used is normative juridical research, which is a library research by examining library materials related to the object under study. The research uses a statute approach. The analysis used in the form of qualitative analysis. The results showed that the regulation and supervision of the procurement, distribution, and use of fertilizers and pesticides in plant cultivation is needed to protect humans from the dangers of chemicals contained in plants due to excessive use of fertilizers and pesticides. Basically, legal protection is given to protect plant natural resources which have an important role in human life.